EXPLORING THE CORRELATION OF FASTING BLOOD GLUCOSE, SERUM UREA, SERUM CREATININE, AND DIABETES DURATION IN TYPE 2 DIABETIC PATIENTS: A CROSS-SECTIONAL STUDY - Sinha, Anand; Bharty, Rolly (Student's Journal of Health Research Africa, 2024)
Background The relationship between fasting blood glucose (FBG), serum creatinine, serum urea, and the course of diabetes provides crucial insights into the management and progression of type 2 diabetes (T2DM). The study compared the clinical and biochemical characteristics of individuals with T2DM to those of age- and sex-matched healthy controls. Methods Two groups of seventy people were created: thirty-five with a diagnosis of T2DM and thirty-five age- and sex-matched healthy controls. Using conventional laboratory techniques, blood samples were taken to test the levels of serum creatinine, urea, and fasting blood glucose. A significance level of P < 0.05 was applied when performing statistical analysis using the software SPSS-16. Results The mean age of participants was 50 years, with a standard deviation of 8.2 years. The T2DM group had a substantially higher mean fasting blood glucose level (154.7 ± 33.6 mg/dl) than the control group (92.3 ± 10.5 mg/dl) (p < 0.001). Additionally, the T2DM group had higher serum urea levels (32.5 ± 8.1 mg/dl) than the control group (21.6 ± 4.2 mg/dl) (p < 0.01). Comparably, the T2DM group had higher blood creatinine levels (1.2 ± 0.3 mg/dl) than the control group (0.9 ± 0.2 mg/dl) (p < 0.05). Conclusion The study found significant correlations between elevated serum urea, FBG, and serum creatinine levels with the course of diabetes in T2DM patients. These markers are indicative of poor glycemic control and renal impairment, highlighting the importance of regular monitoring and early intervention to prevent complications. Recommendations Early detection and management of diabetic nephropathy requires regular screening of FBG, serum urea, and serum creatinine in T2DM patients. Intensive glycemic control can enhance patient outcomes and minimize diabetes-related kidney damage.